Quantitative analysis of the macroinvertebrate community in the river Temenica (SE Slovenia) - Pust, Mojca (Acta biologica slovenica, 2006)
Macroinvertebrate community of the river Temenica was investigated in order toasses the ecological quality of the stream. Different approaches were used in order to compare their usefulness. Surber sampler methodology was used and all together 16 quantitative samples were taken at four stream reaches every three months from October 2003 until July 2004. Saprobic and diversity indicesshowed severe deterioration of water quality longitudinally and a strong negative influence of the town Trebnje on the ecological state of the river Temenica. Multivariate methods DCA and CCA confirmed those results, but also showed greater differences in community structure at sampling site 1 compared to sites 2 and 3 which was not detected using the indices.
Keywords: ekologija; kakovost voda; ocena kakovosti; saprobni indeks; Temenica; vode